Ability to control emotions of nurses in relation to their jobs - Kalandyk, Halina; Krajewska-Kułak, Elżbieta; Guty, Edyta (Journal of Education, Health and Sport, 2017)
Introduction: The profession of nursing requires mental toughness, stress resistance and ability to cope with difficult situations. Target: Evaluation of the ability to control emotions by nurses, according to their place of work and selected aspects of the nursing proffesion. Material and Methods: The respondents of the survey were 570 nurses. It was performed by diagnostic questionare with a standardized scale of emotional control CECS (Courtauld Emotional Control Scale), Watson and Greer, a Polish adaptation by Juczyński. Results: The average level of anxiety and depression, is about 18 pts., and a little bit less for anger 17 points. It shows few statistically significant connections between evaluation of subjective anger management, anxiety and depression in difficult situations, and the level of satisfaction with some aspects of being a nurse. The only correlations, which have occurred were between being sure about the job security and the level of depression, which was - R = -0.21, between the reconciliation of work and family matters, and the level of depression - R = -0.16, and the evaluation of the relationships with colleagues and a sense of fear - R = - 0.15. A comparative analysis ofthe level of anger (P = 0.6414), depression (p = 0.1220) or anxiety (p = 0.4374) did not confirm statistically significant differencesbetween nurses who work in district hospitals, provincial hospitals and other health care facilities. Conclusion: There were no statistically significant differences in the subjective evaluation of anger management, anxiety and depression in difficult situations and a place of work of the respondents. The strongest correlations were between the level of depression and a sense of job security and reconciliation of work and family matters, and also between evaluation of the relationships with colleagues and a sense of fear.